What’s Next after Psychological Contract Violation? - Guerrero, Sylvie; Naulleau, Mickael (Relations industrielles / Industrial Relations, 2016)
This article adopts an in-depth clinical perspective based on the theoretical framework of grief in order to examine individuals’ reactions following psychological contract violation over a period of 12 months. By focusing on emotional intra-psychic phenomena our study provides evidence of the enduring effects of psychological contract violation on individuals and the employment relationship.We conducted a total of 60 interviews among 11 managers of a temporary employment agency that has implemented a series of organizational changes, mainly related to restructuring and downsizing decisions. The 11 managers interviewed have been chosen after having reported in a short survey that they experienced a psychological contract violation at work.Our results indicate that psychological contract violation triggers the subject into a grief process only when violation deprives the individual from a highly invested object at work. In these circumstances, the grief process lasts longer than we originally expected since, over 12 months, we were unable to observe the grief process in its entirety among our participants. We also find that the grief process may be accelerated or stopped according to the capacity of the organization and the individual to offer new objects that satisfy the individual’s needs and thus may help the person mourn the loss experienced as a result of the violation. Finally, our results show that the grief process deeply alters the employment relationship and modifies the amount and intensity of energy that the participants of our study devote to their work.